The socio-educational impact of virtual social networks on eating disorders - Ortega Navas, María del Carmen; García Pérez, María; Galán Casado, Diego (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Eating disorders are increased among adolescents and young people associated with thinness as a canon of success and beauty. The projection of movements on social networks in contemporary society and the role of influencers have contributed to these disorders having a greater impact on these two most vulnerable populations. The results of this work show that there is a large number of messages and advertisements that encourage people not to eat and go on a diet. The pandemic context has had a negative effect by increasing the symptoms associated with eating dysfunctions.